The role of local language in risk communication: a case study of disaster messaging in Eastern Indonesia - Umma Fathimah Sabilah Faradis (CV Narasi Khatulistiwa Indonesia, 2026)
Background: Disaster communication in multilingual regions of Eastern Indonesia faces challenges due to linguistic diversity and the dominance of national-standard messaging. Objective: This study aims to examine how the use of local languages and culturally embedded signs influences the effectiveness of disaster risk communication in selected high-risk communities. Method: A qualitative approach was employed using semiotic analysis, critical discourse analysis, thematic analysis, and ethnographic content analysis on visual, audio, interview, and community media data. Results: Findings show that disaster messages integrating local language, visual symbolism, and oral narratives significantly enhance clarity, urgency, and trust among recipients. Multimodal communication strategies rooted in cultural familiarity improve comprehension and trigger faster behavioral response during crises. Messages delivered through local media and everyday linguistic expressions are perceived as more legitimate and emotionally resonant than standardized formats. This suggests that localized disaster communication is not only more inclusive but more effective in fostering risk awareness and action. Implications: The study implies that disaster communication policy should institutionalize culturally and linguistically responsive practices to increase resilience and equity in at-risk populations. Novelty: This study offers a novel contribution by integrating multimodal discourse analysis with culturally grounded linguistic practices to demonstrate how localized communication frameworks enhance the effectiveness of disaster risk messaging in multilingual contexts.